The roles of neutrophils in cardiovascular diseases - Lian, Yanjie; Lai, Xiaolei; Wu, Cong; Wang, Li; Shang, JuJu; Zhang, Heyi; Jia, Sihan; Xing, Wenlong; Liu, Hongxu (Frontiers in Cardiovascular Medicine, 2025)
The immune response plays a vital role in the development of cardiovascular diseases (CVDs). As a crucial component of the innate immune system, neutrophils are involved in the initial inflammatory response following cardiovascular injury, thereby inducing subsequent damage and promoting recovery. Neutrophils exert their functional effects in tissues through various mechanisms, including activation and the formation of neutrophil extracellular traps (NETs). Once activated, neutrophils are recruited to the site of injury, where they release inflammatory mediators and cytokines. This study discusses the main mechanisms associated with neutrophil activity and proposes potential new therapeutic targets. In this review, we systematically summarize the diverse phenotypes of neutrophils in disease regulatory mechanisms, different modes of cell death, and focus on the relevance of neutrophils to various CVDs, including atherosclerosis, acute coronary syndrome, myocardial ischemia/reperfusion injury, hypertension, atrial fibrillation, heart failure, and viral myocarditis. Finally, we also emphasize the preclinical/clinical translational significance of neutrophil-targeted strategies.